A Comparative Study of Terminalia chebula (Hezi) in the Theoretical Systems of Traditional Chinese and Tibetan Medicine and Its Modern Scientific Interpretation - Ziyun Zhang; Zhaocong Zhong (Frontiers in Humanities and Social Sciences, 2026)
This study systematically compares the theory and application of Terminalia chebula (Hezi) in Traditional Chinese Medicine (TCM) and Tibetan Medicine. In TCM, Hezi is primarily positioned as an astringent medicinal, mainly used to astringe the lung to suppress cough and astringe the intestines to arrest diarrhea. In Tibetan Medicine, it is revered as the "King of Medicines," broadly regulating the balance of the three humors (rLung, mKhris-pa, and Bad-kan) and is employed for diseases across multiple systems, including digestive, respiratory, nervous, and metabolic disorders, holding a status far beyond its conventional use in TCM. Modern studies indicate that tannin constituents, such as chebulinic acid, exhibit antibacterial, anti-inflammatory, antioxidant, and gut microbiota-modulating activities, providing evidence for traditional efficacy. Furthermore, the "gut–lung axis" mutually corroborates the TCM theory that "the lung and the large intestine are interior–exteriorly related" and the holistic regulatory concept of Tibetan Medicine. However, high-quality clinical evidence is scarce, and the potential hepatotoxic risk of high-dose tannins warrants vigilance. Cross-system comparison can rediscover overlooked values such as tonifying deficiency and moving qi, promoting the integration of traditional medicine with modern science, and offering guidance for new drug development and precision medication.